Health economics in the field of osteoarthritis: an expert's consensus paper from the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO). - Hiligsmann, M; Cooper, C; Arden, N; Boers, M; Branco, J; Luisa Brandi, M; Bruyère, O; Guillemin, F; Hochberg, M; Hunter, D; Kanis, J; Kvien, T; et al. (2013)
OBJECTIVES: There is an important need to evaluate therapeutic approaches for osteoarthritis (OA) in terms of cost-effectiveness as well as efficacy. METHODS: The ESCEO expert working group met to discuss the epidemiological and economic evidence that justifies the increasing concern of the impact of this disease and reviewed the current state-of-the-art in health economic studies in this field. RESULTS: OA is a debilitating disease; it is increasing in frequency and is associated with a substantial and growing burden on society, in terms of both burden of illness and cost of illness. Economic evaluations in this field are relatively rare, and those that do exist, show considerable heterogeneity of methodological approach (such as indicated population, comparator, decision context and perspective, time horizon, modeling and outcome measures used). This heterogeneity makes comparisons between studies problematic. CONCLUSIONS: Better adherence to guidelines for economic evaluations is needed. There was strong support for the definition of a reference case and for what might constitute "standard optimal care" in terms of best clinical practice, for the control arms of interventional studies.